La0.75Sr0.25Cr0.5Mn0.5O3-δ as cathode for electrolysis and co-electrolysis of CO2 and H2O in solid oxide electrolysis cell. Issue 16 (15th August 2021) - Ma, Zheng; Li, Yongyong; Zheng, Yifeng; Li, Wenlu; Chen, Xingyu; Sun, Xiufu; Chen, Xing; Zhou, Juan
Abstract: The cathode of solid oxide electrolysis cell (SOEC) is used as a place for fuel gas electrolysis/co-electrolysis, and its performance significantly affects the efficiency of electrolysis. La0.75 Sr0.25 Cr0.5 Mn0.5 O3-δ (LSCM) is a potential SOEC cathode material due to its excellent redox stability and catalytic ability for fuel gas. An electrolyte-supported LSCM/YSZ/LSCM symmetrical cell and LSCM/YSZ/LSCF full cell were prepared and evaluated for high temperature steam electrolysis, carbon dioxide electrolysis and co-electrolysis. Under the applied voltage, both the symmetrical electrolysis cell and the full electrolysis cell can effectively electrolysis CO2 and H2 O. During the experiment, by changing the operating conditions, the influence of different temperatures, concentration of CO2 and H2 O, and applied voltage was studied to evaluate the electrochemical performance of SOEC. In order to further verify the long-term performance of SOEC, constant voltage was applied for co-electrolysis of CO2 and H2 O. During the entire electrolysis process, the SOEC showed a stable current density of 0.1A·cm -2 under the applied voltage 1.5 V for more than 24 h.